Dad dad buu dugsadaa dugaagna geed – the Somali Diaspora in the United States and their Impact on the American Domestic, Social and Security Situation - Marta Antosz (Ksiegarnia Akademicka Publishing, 2021)
The paper is dedicated to the Somali diaspora in the United States and its influence on the American domestic, social and security situation in relation to: 1) Somali cultural, historical and religious background, 2) history and patterns of U.S. Somali immigration, 3) analysis of the Somali cultural adaptation to American society, 4) analysis of the remittances sent from diaspora back home and certain associated patterns 5) potential among Somalis, especially young Somalis, when it comes to the Islamic radicalization, 6) analysis of the Somalis as part of Black African immigration. However, Somalis are not even close to being the largest migration group from Sub‑Saharan Africa, for sure they are a significant one. Settled mostly in Minnesota (mostly the Minneapolis urban area), Columbus (Ohio), Seattle (Washington), Virginia, Washington D.C. metropolitan area, New York City metropolitan area, San Diego and Georgia, they created a unique minority with significant impact on the whole picture of American society and the American domestic and security situation.